Utilization of The Sayeung Mangrove Edu-Tourism Area, Gampong Baro Sayeung Village, Setia Bakti District, Aceh Jaya Regency. Aceh Province as an Environmental Literacy-Based Learning Resource in Elementary Schools - Kurniadi, Muhammad Dwi; Astuti, Fuji; Fajri, Ahmad (Honoli of Journal Primary Teacher Education, 2026)
This study aims to examine environmental literacy-based learning practices at the Sayeung Mangrove Edu-Tourism Area, Gampong Baro Sayeung Village, Setia Bakti District, Aceh Jaya Regency, Aceh Province, which are integrated into the Merdeka Curriculum learning outcomes as a learning resource to develop environmentally literate students at the elementary school level. Descriptive qualitative research with a case study method was chosen as the approach for this study. Observation, interviews, and documentation were employed as data collection techniques. Data reduction, data presentation, and verification served as data analysis techniques. The Sayeung Mangrove Edu-Tourism Area can be utilized by implementing the principles of experiential learning, expedition, and project-based learning. These principles align with one of the key characteristics of the Merdeka Curriculum, namely project-based learning for developing soft skills and character in accordance with the Pancasila Student Profile, differentiated according to students’ abilities and adapted to local context and content. Environmental literacy practices at the Sayeung Mangrove Edu-Tourism Area are integrated with the Merdeka Curriculum Learning Outcomes for lower and upper elementary grades, which can be implemented through lesson plans that promote environmental literacy.